Pengaruh Internet Terhadap Hasil Pemberian Tugas Belajar Matematika Sekolah Dasar Se-Kota Metro - Yunita Wildaniati (Jurnal Dewantara, 2020)
One form of technology that is seen as being able to provide an impetus to the world of education is the world of the internet which at this time has become something that is no longer foreign to the community, especially in the world of education. Based on the results of the data analysis that the authors obtained, in this case the authors can conclude as follows: There is a significant influence between the internet on the learning tasks of elementary school students in Kota Metro. By using a db of 4, it can be obtained that the table chi square value for a significant level of 5% is 9.488, and for a significant level of 1% it is 13,227. Thus, at the 1% significant level and at the 5% significance level or 9.488 < 20.3507 > 13,227. It means that the hypothesis (Ha) that the author proposes in this study is accepted and rejects the null hypothesis (Ho). Thus, the authors can conclude that: there is a positive influence of the internet on the learning tasks of elementary school students in Kota Metro.